A CAPOEIRA DE BRAÇOS PARA O AR Um Estudo da Capoeira Gospel no ABC Paulista - Brito, Diolino Pereira de (2007)
Abstract The subject of this research is the changing process currently being experienced by capoeira thanks to the phenomenon of christian capoeira in the ABC region of São Paulo and its environs. It is discussed how christians of evangelical denomination have been using capoeira as a preaching tool and how they incorporate its body language as part of the african-brazilian cultural heritage. Field research was conducted through semi-structured interviews with evangelical preachers, preachers who are also capoeira masters, and capoeira practitioners in Pentecostal and neo-Pentecostal temples as well as nonreligious schools. The christian capoeira movement is a recent and rising phenomenon. With its principles based on the Bible, it deconstructs the common notions of secular capoeira, originally based on a set of traditional, african-born myths, rituals and sports.(AU)